Power supplies and equipment for military field research: lessons from the British Service Dhaulagiri Research Expedition 2016. Issue 1 (25th December 2017) - Howard, Matt; Bakker-Dyos, J; Gallagher, L; O'Hara, J P; Woods, D; Mellor, A
Abstract : Introduction: The British Service Dhaulagiri Research Expedition (BSDMRE) took place from 27 March to 31 May 2016. The expedition involved 129 personnel, with voluntary participation in nine different study protocols. Studies were conducted in three research camps established at 3600, 4600 and 5140 m and involved taking and storing blood samples, cardiac echocardiography and investigations involving a balance plate. Research in this remote environment requires careful planning in order to provide a robust and resilient power plan. In this paper we aim to report the rationale for the choices we made in terms of power supply, the equipment used and potential military applicability. Methods: This is a descriptive account from the expedition members involved in planning and conducting the medical research. Results: Power calculations were used to determine estimates of requirement prior to the expedition. The primary sources used to generate power were internal combustion engine (via petrol fuelled electric generators) and solar panels. Having been generated, power was stored using lithium-ion batteries. Special consideration was given to the storage of samples taken in the field, for which electric freezers and dry shippers were used. All equipment used functioned well during the expedition, with the challenges of altitude, temperature and transport all overcome due to extensive prior planning. Conclusions: Power was successfully generated, stored and delivered during the BSDMRE, allowing extensive medical research to be undertaken. The challenges faced and overcome are directly applicable to delivering military medical care in austere environments, and lessons learnt can help with the planning and delivery of future operations, training exercises or expeditions.